Gorham Stout syndrome in a pediatric patient. A case report - Ariel Moya Machado; Leidelén Esquivel Sosa; Yisel González Ríos (Medisur)
Within the idiopathic osteolysis syndromes classification, Gorham-Stout disease ranks fourth. It is a clinical picture characterized by the progressive destruction of bone tissue and vascular proliferation, with angiomatosis and bone lymphangiomatosis that produces a progressive osteolysis of the skeleton, with loss of bone mass in the affected areas. This article aims to present a pediatric patient with Gorham Stout syndrome treated at the José Luis Miranda University Pediatric Provincial Hospital in Villa Clara. A 2-years-old female patient with a one week fever evolution, increased volume in the dorsal region and weight loss. The physical examination revealed cutaneous-mucosal pallor and a three centimeters painless nodular lesion in the dorsal region. The fever recurred and a marked increase in volume was observed in the dorsal lumbar region. Computed axial tomography and magnetic resonance imaging revealed osteolysis of the vertebral bodies from D8 to L2 and an increase in the adjacent soft tissues. The clinical and imaging manifestations made it necessary to dismiss infectious and neoformative etiologies. The former were dismissed and because they fulfill the required criteria it was concluded as Gorham's disease. This is a rare and peculiar musculoskeletal pathological condition in which bone virtually disintegrates and is replaced by vascular connective tissue. Its etiology is speculative, with a highly variable clinical presentation. Imaging studies are very useful. It has an indeterminate prognosis despite the therapeutic options used. Because it is an extremely rare syndrome, the presentation of the case was decided.